Program approbation of psychological readiness optimization of mobilized persons for military service - Nikitenko, Hanna (Psychological Prospects Journal, 2019)
The article represents the results of the author's program approbation of social and psychological readiness optimization of mobilized persons for military service using the resource approach strategies (development of psychological sustainability, increase of self-regulation level, formation of motivational and instrumental resources). It was established with the help of Wilcoxon T-test that the “development of psychological sustainability” unit showed the increase of life sustainability level, involvement, the ability to enjoy own activity; we succeeded in reinforcement of positive attitude towards uncertainty and complex tasks. “Increase of self-regulation level” unit showed strengthening of willingness acceptance to take risks; reducing the level of positive attitude to negative situations; reducing the level of socio reflection, the level of asocial strategies to overcome stress (the aggressive actions level). The unit “formation of motivational and instrumental resources”showed increase of general level of uncertainty acceptance; we succeeded in strengthening of ability feeling to control one's own temper; increased the search of social support for solving stressful situations, herewith decreased the level of self-confidence, intention to avoid stressful situations, decreased the level of use of manipulations, cruelty, cynicism, aggressive actions, pressure, refusal to find alternative ways out of difficult situations. The stressful situation constructive strategies usage level increased. The effectiveness of the author's program of social and psychological training on optimization of psychological readiness of mobilized persons for military service was confirmed.